Peran Supervisi Pembelajaran dalam Meningkatkan 10 Kompetensi Pedagogik Guru di SDN Katulampa 04 - Muslih Musolihat; Siti Qomariyah; Alfian Khadafi (Lembaga Pengembangan Kinerja Dosen, 2025)
Behind the importance of a teacher's role in the progress of a nation comes a weighty responsibility. Teachers are expected to be able to master the skills required to make the teacher profession a professional. In Indonesia education systems has been governed the competence that a teacher must maintain his duty while linked to the implementation of a supervision, to which this writing is the answer to the problem. For research methods, researchers use descriptive qualitative methods. Interviews, observation and documentation as data collection. And the miles and hubberman technique as the data analysis technique, with procedure 1) data reduction, 3) data presentation and 4) data verification, 2) powerability and 3) dependability as far as the results of this study are 1) education supervision is the development and monitoring activities that are done to help teachers and educators improve the quality of education, 2) supervision of learning at SDN katulampa 04 times a month, 3) supervision plays an important role in making it easier for teachers to improve teaching ability and reduce barriers to learning.